Dentures may be radiolucent. Issue 6 (17th November 2003) - Firth, A L; Moor, J; Goodyear, P W A; Strachan, D R
Abstract : Diagnosing ingested dental prostheses can be difficult and delays in treatment may result in serious complications. Patients often present with a vague history and very few reliable clinical signs. In addition, the fact that dental plates are often radiolucent may lead to the diagnosis being overlooked with disastrous consequences. A case of successful diagnosis and treatment is presented, and the importance of a high index of clinical suspicion to avoid the morbidity and mortality associated with missed impacted dentures is discussed.